Randomized clinical studies assessing the pharmacokinetics and subjective effects of vuse alto electronic nicotine delivery systems - Kristen Prevette; Kristen G. Jordan; Brian M. Keyser; Milly N. Kanobe; Tao Jin; Sarah Ayoku; John Darnell; Patrudu Makena; Sarah A. Baxter (Scientific Reports)
Abstract The US FDA recommends assessment of abuse liability (AL) for premarket tobacco product applications (PMTAs) to determine whether a new tobacco product is appropriate for the protection of public health (APPH). To assess the AL and nicotine uptake of Vuse Alto electronic nicotine tobacco products (ENDS) which offer e-liquid pods that vary in nicotine concentration, we conducted two clinical laboratory studies. The primary objective of Study 1 was to assess measures of product abuse liability (AL) in real time during and following product use. This was achieved through timed subjective effect questionnaires, physiological measures (blood pressure and heart rate), and pharmacokinetic assessments for Golden Tobacco flavor 2.4% and 5% nicotine concentration Vuse Alto products. Study 2 evaluated PK and Overall Product Liking (OPL) of four Alto flavor variants with 1.8% and 2.4% nicotine concentrations. The studies were designed as open-label, randomized, crossover studies with 9 and 7 days of confinement for Study 1 and Study 2 respectively, were employed to assess nicotine PK, subjective effects, and physiological measures (Study 1 only) for 4 h after a 10-minute ad libitum ENDS product use. Study 1 included high (usual brand [UB] cigarettes) and low abuse liability (nicotine gum) comparators. Nicotine PK of Vuse Alto products were generally similar across the three nicotine concentrations and four flavors tested in these studies. In Study 1, nicotine PK and several subjective effects (product liking, OPL, product positive/negative effects and urge to smoke) for Vuse Alto 2.4% and 5% products were determined to be in between UB cigarettes and nicotine gum. Increases in heart rate, systolic and diastolic blood pressure were observed for both products. In Study 2, nicotine PK and the OPL for Vuse Alto four flavors at 1.8% and Golden Tobacco at 2.4% were similar and comparable to the Alto products tested in Study 1. These results indicate the AL of Vuse Alto, as assessed by nicotine PK and subjective effects measures of Vuse Alto products at three nicotine concentrations and of four flavors, is significantly lower than cigarettes, and higher than nicotine gum. ENDS products deliver nicotine in a manner that satisfies smokers’ preferences while exhibiting lower AL than cigarettes. Compared to pharmaceutical smoking cessation aids, such as nicotine gum, the Vuse Alto products demonstrate nicotine PK profiles characterized by a more rapid onset and higher peak concentrations, with subjective measures such as product liking, fall between those of nicotine replacement therapy gum and combustible cigarettes. Collectively, the AL assessments indicate that Vuse Alto products may support tobacco harm reduction by providing an alternative that may help smokers migrate away from cigarette smoking.